Endoscopy for Pediatric Retinal Disease. Issue 3 (May 2018) - Yeo, Damien C.M.; Nagiel, Aaron; Yang, Unikora; Lee, Thomas C.; Wong, Sui Chien
Abstract : Abstract: : Endoscopic vitrectomy is a useful and unique adjunct to microincision vitreoretinal surgery. The optical properties of endoscopy allow for some clinically advantageous approaches that are not possible with regular microscope viewing systems, namely, the ability to both bypass optically significant anterior segment opacities and directly visualize difficult‐to‐access retroirideal, retrolental, and anterior retinal structures in their natural anatomical configuration. The surgical benefits include improved surgical access to the pars plana, pars plicata, ciliary sulcus, ciliary body, and peripheral lens, along with unique access to anterior traction in complex pediatric anterior retinal detachments, particularly in retinopathy of prematurity. This review will focus on the development and surgical utility of intraocular endoscopy, provide an update on its current uses in the era of microincision vitreoretinal surgery, and highlight its role in pediatric vitreoretinal diseases.